COVID‐19 in solid organ transplant recipients: a single‐center experience. (26th June 2020) - Hoek, Rogier A. S.; Manintveld, Olivier C.; Betjes, Michiel G. H.; Hellemons, Merel E.; Seghers, Leonard; Van Kampen, Jeroen A. A.; Caliskan, Kadir; van de Wetering, Jacqueline; van den Hoogen, Martijn; Metselaar, Herold J.; Hesselink, Dennis A.; ,
Summary: Solid organ transplant (SOT) recipients may be at risk for severe COVID‐19. Data on the clinical course of COVID‐19 in immunosuppressed patients are limited, and the effective treatment strategy for these patients is unknown. We describe our institutional experience with COVID‐19 in SOT. Demographic, clinical, and treatment data were extracted from the electronic patient files. A total of 23 SOT transplant recipients suffering from COVID‐19 were identified ( n = 3 heart; n = 15 kidney; n = 1 kidney‐after‐heart; n = 3 lung, and n = 1 liver transplant recipient). The presenting symptoms were similar to nonimmunocompromised patients. Eighty‐three percent (19/23) of the patients required hospitalization, but only two of these were transferred to the intensive care unit. Five patients died from COVID‐19; all had high Clinical Frailty Scores. In four of these patients, mechanical ventilation was deemed futile. In 57% of patients, the immunosuppressive therapy was not changed and only three patients were treated with chloroquine. Most patients recovered without experimental antiviral therapy. Modification of the immunosuppressive regimen alone could be a therapeutic option for SOT recipients suffering from moderate to severe COVID‐19. Pre‐existent frailty is associated with death from COVID‐19.